The Development of Android-Based Instructional Media Utilizing an Expert System for the Engine Simulator Course - Basir, Abdul; Ansar, Ince; Alam, Syamsu; Maulana, Reza; S Gassing, Al Fadli Ramdani; Nur Indah, Araya (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the integration of technology, particularly Android-based applications combined with expert systems, in vocational education at the Makassar Maritime Polytechnic. The application is designed to assist cadets in understanding ship machinery through interactive simulations that facilitate the detection of issues in main propulsion engines. The findings indicate that simulator-based learning provides convenience but is not yet capable of detecting problems in detail. The use of Android-based applications is expected to support cadets’ decision-making in addressing industrial challenges and enhance the quality of education to better align with the demands of the business and industrial sectors.